Law Enforcement At Sea Hinders Sea Toll Program Towards Indonesia As A Global Maritime State - Karolus Geleuk Sengadji; Amin Purnawan; Aryani Witasari (Law Development Journal, 2021)
The purpose of this research is to identify and analyze obstacles to shipping activities and solutions for law enforcement at sea to support shipping activities/sea tolls programs. The specification of this research is descriptive analytical, and the approach to the problem is carried out in a normative juridical manner, to examine national and international laws and regulations in the shipping sector. The data used are secondary data from primary legal materials, secondary legal materials and tertiary legal materials, which are collected through literature study, and analyzed using qualitative analysis methods, and presented described descriptively. The results of the study indicate that the obstacles in shipping activities/sea tolls programs are the many law enforcement agencies at sea which have overlapping authority to stop and inspect ships at sea, so the best solution is to have an integrated security system under one civil institution to be effective and efficien  to support the smooth running of the sea tolls program.